Utilizing the Delphi method to develop parent and child surveys to understand exposure to farming hazards and attitudes toward farm safety - Jessie Adams; Jessie Adams; Alison Kennedy; Alison Kennedy; Jacquie Cotton; Jacquie Cotton; Susan Brumby; Susan Brumby (Frontiers Media S.A., 2022)
Children on farms are at increased risk of injury. In Australia, children under 15 years consistently represent ~15% of all farm-related fatalities. This study aimed to develop parent and child surveys to gain a greater understanding of children's (5-14 years) exposure to occupational risk on farms by exploring their exposure to farm hazards, risk-taking behavior, their use and attitudes toward safety measures, and experience of farm-related injury. As farming communities are heterogeneous, a modified Delphi method was undertaken to ensure input from a diverse group. Seventeen experts participated in a three round process-the first two rounds required rating of proposed survey questions in an online questionnaire and the final round was an online discussion. Consensus was defined as 75% agreement or higher. This process resulted in 155 parent questions and 124 child questions reaching consensus to include. The modified Delphi method developed surveys that provide insight into the behaviors and attitudes of children (individuals) and their parents on farms (family) and will assist in informing how community, organizations and policy frameworks can improve child safety on farms. It will assist in identifying and understanding common farming exposures/behaviors of children and their parents to inform the development of targeted and culturally appropriate injury prevention strategies. As farming groups are heterogeneous, these survey scan be used on varying farming cohorts to identify their unique farming hazards and challenges. Child farm-related injuries are a problem globally and must be addressed; children are dependent on adults and communities to create safe environments for them.